Wyn Grant (ed.), Businesse Interests, Organizational Development and Private Interest An International Comparative Study of the Food Processing Industry, - New York: Walter de Gruyter, 1987,232 s., 51.75; Hajo Weber, Unternehmerverbände zwischen Markt, - Ronit, Karsten (Politica, 1988)
Wyn Grant (ed.), Businesse Interests, Organizational Development and Private Interest An International Comparative Study of the Food Processing Industry, - New York: Walter de Gruyter, 1987,232 s., 51.75; Hajo Weber, Unternehmerverbände zwischen Markt, Staat und Gewerkschaften. Zur intermediären von Wirtschaftsinteressen, Frankfurt - New York: Campus Verlag, s., DM 55,00.